ANALISIS DESKRIPTIF RETORIKA INTERPERSONAL PRAGMATIK PADA TUTURAN DIREKTIF GURU DAN SISWA DALAM PEMBELAJARAN BAHASA INDONESIA DI KELAS XI SMA (SLUA) SARASWATI 1 DENPASAR - Cahyani, Ni Komang Triulan; Erawan, Dewa Gede Bambang; Suparsa, I Nyoman (Prodi Pendidikan Bahasa dan Sastra Indonesia FKIP Unmas Denpasar, 2024)
The aims of this research include three things: (1) the function of pragmatic interpersonal rhetoric in teacher and student directive speech, (2) the form of pragmatic interpersonal rhetoric in teacher and student directive speech, and (3) factors that influence pragmatic interpersonal rhetoric in directive speech. teacher and student. The subjects of this research consisted of a teacher and students learning Indonesian in class XI.1. The data collection methods used in this research are observation, recording and interview methods. Data analysis was carried out in three stages, namely (1) data reduction, (2) data presentation, and (3) drawing conclusions. The results of this research show that (1) the function of pragmatic interpersonal rhetoric in teachers' and students' directive speech is requertives (asking and requesting), permissive (giving permission, granting and permitting), advice (suggesting, warning, advising, encouraging, and measuring), requirements (event), question (ask), and prohibition (forbid). (2) forms of pragmatic interpersonal rhetoric in imperative, interrogative and declarative teacher and student directive speech. (3) factors that influence pragmatic interpersonal rhetoric in teacher and student directive speech, the social distance factor between the speaker and the interlocutor (the speaker has a higher position), the communication situation factor, and the purpose of the speech by showing the speaker's sympathy.